Real-World Evidence on Prognostic Value of MRD in Multiple Myeloma Using Flow Cytometry - Muronova, Ludmila; Soucek, Ondrej; Zihala, David; Sevcikova, Tereza; Popkova, Tereza; Plonkova, Hana; Venglar, Ondrej; Pour, Ludek; Stork, Martin; Rihova, Lucie; Bezdekova, Renata; Minarik, Jiri; et al. (European journal of haematology, 2025)
Minimal residual disease (MRD) is one of the most important prognostic factors in multiple myeloma (MM) and a valid surrogate for progression-free survival (PFS) and overall survival (OS). Recently, MRD negativity was approved as an early clinical endpoint for accelerated drug approval in MM. Nevertheless, there is limited evidence of MRD utility in real-world setting. In this retrospective multicenter study, we report outcomes of 331 newly diagnosed MM patients with MRD evaluation at Day+100 after autologous stem cell transplantation using flow cytometry with a median limit of detection of 0.001%. MRD negativity was reached in 47% of patients and was associated with significantly prolonged median PFS (49.2 months vs. 18.4 months; hazard ratios (HR) = 0.37; p < 0.001) and OS (not reached vs. 74.9 months; HR = 0.50; p = 0.007). Achieving MRD negativity was associated with PFS improvements regardless of age, International Staging System (ISS) stage, lactate dedydrogenase (LDH) level, or cytogenetic risk. Importantly, MRD positive patients benefited from lenalidomide maintenance versus no maintenance (18-months PFS: 81% vs. 46%; HR = 0.24; p = 0.002) while in MRD negative patients such benefit was not observed (p = 0.747). The outcomes of our real-world study recapitulate results from clinical trials including meta-analyses and support the idea that MRD positive patients profit more from lenalidomide maintenance than MRD negative ones.
Keywords: dospělí; Lenalidomide; lenalidomid; Prognosis; retrospektivní studie; Humans; staging nádorů; lidé středního věku; Neoplasm Staging; Middle Aged; Hematopoietic Stem Cell Transplantation; Neoplasm, Residual; reziduální nádor; Multiple Myeloma; prognóza; mužské pohlaví; Flow Cytometry; transplantace hematopoetických kmenových buněk; Adult; výsledek terapie; průtoková cytometrie; autologní transplantace; Treatment Outcome; ženské pohlaví; lidé; Aged; senioři; mnohočetný myelom; Male; Retrospective Studies; Transplantation, Autologous; Female